Prognostic performance of multiple biomarkers in patients with acute coronary syndrome without standard cardiovascular risk factors - Wang, Le; Cong, Hong-liang; Zhang, Jing-xia; Li, Xi-ming; Hu, Yue-cheng; Wang, Chen; Lang, Jia-chun; Zhou, Bing-yang; Li, Ting-ting; Liu, Chun-wei; Yang, Hua; Ren, Li-bin; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background and Aims: Acute coronary syndrome (ACS) without standard modifiable cardiovascular risk factors (SMuRFs) represents a special case of ACS. Multiple biomarkers have been shown to improve risk stratification in patients with ACS. However, the utility of biomarkers for prognostic stratification in patients with ACS without SMuRFs remains uncertain. The aim of the present study was to evaluate the prognostic value of various biomarkers in patents with ACS without SMuRFs. Methods: Data of consecutive patients with ACS without SMuRFs who underwent coronary angiography in Tianjin Chest Hospital between January 2014 and December 2017 were retrospectively collected. The primary outcome was the occurrence of major adverse cardiovascular event (MACE), defined as a composite of cardiovascular death, myocardial infarction and stroke. Seven candidate biomarkers analyses were analyzed using models adjusted for established risk factors. Results: During a median 5-year follow-up, 81 of the 621 patients experienced a MACE. After adjustment for important covariates, elevated fibrinogen, D-dimer, N-terminal proB-type natriuretic peptide (NT-proBNP), and lipoprotein (a) [Lp(a)] were found to be individually associated with MACE. However, only D-dimer, NT-proBNP and Lp(a) significantly improved risk reclassification for MACE (all P<0.05). The multimarker analysis showed that there was a clear increase in the risk of MACE with an increasing number of elevated biomarkers and a higher multimarker score. The adjusted hazard ratio- for MACE (95% confidential intervals) for patients with 4 elevated biomarkers was 6.008 (1.9650–18.367) relative to those without any elevated biomarker-. Adding- the 4 biomarkers or the multimarker score to the basic model significantly improved the C-statistic value, the net reclassification index and the integrated discrimination index (all P<0.05). Conclusion: Fibrinogen, D-dimer, NT-proBNP and Lp(a) provided valuable prognostic information for MACE when applied to patients with ACS without SMuRFs. The multimarker strategy, which combined multiple biomarkers reflecting different pathophysiological process with traditional risk factors improved the cardiovascular risk stratification.